Randomized Controlled Clinical Trial of Bivalent Oral Poliovirus Vaccine and Inactivated Poliovirus Vaccine in Nigerian Children. (24th November 2020) - Tagbo, Beckie N; Verma, Harish; Mahmud, Zubairu M; Ernest, Kolade; Nnani, Roosevelt O; Chukwubike, Chinedu; Craig, Kehinde T; Hamisu, Abdullahi; Weldon, William C; Oberste, Steven M; Jeyaseelan, Visalakshi; Braka, Fiona; et al.
Abstract: Background: We conducted a trial in Nigeria to assess the immunogenicity of the new bivalent oral poliovirus vaccine + inactivated poliovirus vaccine (bOPV+IPV) immunization schedule and gains in type 2 immunity with addition of second dose of IPV. The trial was conducted in August 2016–March 2017, well past the trivalent OPV-bOPV switch in April 2016. Methods: This was an open-label, 2-arm, noninferiority, multicenter, randomized, controlled trial. We enrolled 572 infants aged ≤14 days and randomized them into 2 arms. Arm A received bOPV at birth, 6, and 10 weeks, bOPV+IPV at week 14, and IPV at week 18. Arm B received IPV each at 6, 10, and 14 weeks and bOPV at 18 weeks of age. Results: Seroconversion rates for poliovirus types 1 and 3, respectively, were 98.9% (95% confidence interval [CI], 96.7–99.8) and 98.1% (95% CI, 88.2–94.8) in Arm A and 89.6% (95% CI, 85.4–93.0) and 98.5% (95% CI, 96.3–99.6) in Arm B. Type 2 seroconversion with 1 dose IPV in Arm A was 72.0% (95% CI, 66.2–77.3), which increased significantly with addition of second dose to 95.9% (95% CI, 92.8–97.9). Conclusions: This first trial on the new Expanded Program on Immunization (EPI) schedule in a sub-Saharan African country demonstrated excellent immunogenicity against poliovirus types 1 and 3 and substantial/enhanced immunogenicity against poliovirus type 2 after 1 to 2 doses of IPV, respectively. Abstract : We demonstrated high immunogenicity of the new bOPV+IPV EPI-schedule in infants. Only data from sub-Saharan African country on immunogenicity of bOPV+IPV schedule compared with IPV alone. Critical information on added protective value of 2IPV doses compared with 1 dose.